2013
DOI: 10.1074/jbc.m113.478503
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors SOX4 and SOX11 Function Redundantly to Regulate the Development of Mouse Retinal Ganglion Cells

Abstract: Background:Roles of SoxC genes in the development of retinal ganglion cells (RGCs) are unknown at present. Results: Targeted deletion of Sox4 and Sox11 in retina results in a complete loss of RGCs. Conclusion: Sox4 and Sox11 function redundantly to regulate RGC development. Significance: These findings highlight the essential role of SoxC genes in retinal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 43 publications
7
111
0
Order By: Relevance
“…To verify that these phenotypes were due to loss of Tbr2 in the retina, we stained P1 brains for Tbr2 in retinal targets and found no Tbr2 ϩ cells in the OPN, IGL, LGN, or PPN; however, consistent with previous reports (Bulfone et al, 1999;Kimura et al, 1999), labeled cells were found in the hippocampus (data not shown).…”
Section: Tbr2 Is Required For the Formation Of Retinal Projections Tosupporting
confidence: 61%
See 2 more Smart Citations
“…To verify that these phenotypes were due to loss of Tbr2 in the retina, we stained P1 brains for Tbr2 in retinal targets and found no Tbr2 ϩ cells in the OPN, IGL, LGN, or PPN; however, consistent with previous reports (Bulfone et al, 1999;Kimura et al, 1999), labeled cells were found in the hippocampus (data not shown).…”
Section: Tbr2 Is Required For the Formation Of Retinal Projections Tosupporting
confidence: 61%
“…Therefore, differentiation from progenitor cells is significantly influenced by the regulated expression of transcription factors (Shirasaki and Pfaff, 2002). Numerous transcription factors, many of which control cell fate in the nervous system and elsewhere, are expressed in RGCs (Brown et al, 2001;Mu and Klein, 2004;Badea et al, 2009;Jiang et al, 2013), although none have been linked directly to specific RGC functional types and accompanying neural circuits. Here, we show that Tbr2 (also known as Eomesodermin), a T-box transcription factor that plays a critical role in the development of neural and non-neural tissues (Russ et al, 2000;Arnold et al, 2008;Mao et al, 2008;Sessa et al, 2008), is essential for the specification of RGC types that participate in non-imageforming visual circuits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key regulators for RGC development include Atoh7 (also known as Math5), Pou4f2, and Isl1, with Atoh7 functioning upstream, and Pou4f2 and Isl1 downstream (32). Sox4 and Sox11 also seem to be involved in the early stages of RGC genesis, downstream of Atoh7 but independent of Pou4f2 (33). Oc1 and Oc2 are both expressed in RPCs and postmitotic RGCs, and thus appear to function at two levels: one during RGC genesis (at the same level as Atoh7) and the other after RGC genesis (downstream of Atoh7) to regulate RGC subtype specification (15).…”
Section: Potential Mechanisms By Which Oc1 and Oc2 Function In Multiplementioning
confidence: 99%
“…Animals-Generation of the Sox11 fx/fx mice has been described previously (28). Mouse strains for Wnt1-Cre, Dermo1-Cre, Osr2-IRESCre, K14-Cre, Foxg1-Cre, Nestin-Cre, and EIIaCre were purchased from The Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%